Molecular genetic assessment of jatrophacurcas l. Germplasm of diverse origin along with its wild Relatives for various early growth and Establishment related traits - K.V.N. RATHNAKAR REDDI; A. KRISHNA SATYA; P. RAMESH; SIVARAM P. LEKKALA; K. NARENDRA; P. CHANDRA OBUL REDDY; C. V. C. M. REDDY; A. CHANDRA SEKHAR (International Journal of Pharma and Bio Sciences, 2016)
Jatropha curcas L. is promising crop with drought tolerance and potential crop for biodiesel. In present study, 33 accessions of Jatropha curcas L. were collected from different eco-climatic zones along with two wild relatives, J. foetida and J. gossypifolia, were screened for genetic diversity using RAPD and ISSR markers. Further the same has been evaluated for their ability for early field establishment on the basis of phenotypic parameter. Out of 25 RAPD and 14 ISSR primers, 16 RAPD and 6 ISSR primers gave reproducible amplification banding patterns with total 88 polymorphic bands across genotypes. The polymorphic information content was highest for the primer OPB 10 (0.43) followed by the primers OPH 7 (0.42). UPGMA cluster analysis of genetic similarity indices grouped all the accessions into four major groups. Jaccard’s coefficient of similarity varied from 0.42 to 0.97, indicating high level of genetic variation across genotypes under study. Significant phenotypic variation in terms of total chlorophyll content, growth and establishment across genotypes was also observed. Present study highlights collection, conservation and characterization of potential Jatropha genetic resources and their utilization as breeding materials for their growth and early establishment in field conditions.